Microfluidic Biofabrication of 3D Multicellular Spheroids by Modulation of Non-geometrical Parameters - Lopa, Silvia; Piraino, Francesco; Talò, Giuseppe; Mainardi, Valerio Luca; Bersini, Simone; Pierro, Margherita; Zagra, Luigi; Rasponi, Marco; Moretti, Matteo (Frontiers in Bioengineering and Biotechnology, 2020)
Three-dimensional (3D) cell spheroids are being increasingly applied in many research fields due to their enhanced biological functions as compared to conventional two-dimensional (2D) cultures. 3D cell spheroids can replicate tissue functions, which enables their use both as in vitro models and as building blocks in tissue biofabrication approaches. In this study, we developed a perfusable microfluidic platform suitable for robust and reproducible 3D cell spheroid formation and tissue maturation. The geometry of the device was optimized through Computational Fluid Dynamic (CFD) simulations to improve cell trapping. Experimental data were used in turn to generate a model able to predict the number of trapped cells as a function of cell concentration, flow rate and seeding time. We demonstrated that tuning non-geometrical parameters it is possible to control the size and shape of 3D cell spheroids generated using articular chondrocytes as cellular model. After seeding, cells were cultured under perfusion at different flow rates (20, 100 and 500 µl/min), which induced the formation of conical and spherical spheroids. Wall shear stress values on cell spheroids, computed by CFD simulations, increased accordingly to the flow rate while remaining under the chondroprotective threshold in all configurations. The effect of flow rate on cell number, metabolic activity and tissue-specific matrix deposition was evaluated and correlated with fluid velocity and shear stress distribution. The obtained results demonstrated that our device represents a helpful tool to generate stable 3D cell spheroids which can find application both to develop advanced in vitro models for the study of physio-pathological tissue maturation mechanisms as well as to obtain building blocks for the biofabrication of macrotissues.